Parcel Delivery & Journey Companion Finder - Anouska Kashyap; Madhavi Sen; Mihika Jain; Shreya Singh; Sanjeev Patwa (International Journal of Computer Science Languages, 2024)
The idea of the project is to provide an interactive platform for people to help each other to carry their parcels from one place to another. The platform even provides a feature for finding a travel companion for the journey and thus helps in reducing their expenses. The parcel delivery and journey companion finder is a web-based system designed primarily for the users, so that they can find parcel services and journey companion finder service at one platform. This will help the users to lower their travel expenses through carpooling and they can also send their parcels faster as compared to courier services. The project was developed using PHP, CSS, HTML, and MYSQL. The system is an online application and can be hosted online, so users may need an internet connection or the company's local network.
Keywords: API key; Carpooling; Database; journey companion; parcel